2010
DOI: 10.1038/cgt.2010.71
|View full text |Cite
|
Sign up to set email alerts
|

Dlxin-1, a member of MAGE family, inhibits cell proliferation, invasion and tumorigenicity of glioma stem cells

Abstract: We have previously reported the presence of Dlxin-1, a member of the melanoma antigen gene (MAGE) family, in the brain and showed its function as a cell cycle arrest protein, suggesting that Dlxin-1 may have anti-proliferative functions in rapidly growing tumors. Using the cancer stem cell hypothesis, which attributes the initiation and progression of brain tumors to the cancerinitiating stem cells, we have investigated the role of Dlxin-1 in the glioma stem cells propagated by us as a cell culture system comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
(48 reference statements)
2
9
0
Order By: Relevance
“…During the past decade, emerging evidence supports the notion that CSCs are responsible for tumor development including tumor initiation, invasion, angiogenesis, therapy resistance, and recurrence [33][35]. GSCs have been demonstrated to be highly invasive [36], [37]. In fact, invasive glioma cells show tumor stem cell characteristics with neurosphere formation ability and tumorigenicity [34], [38].…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, emerging evidence supports the notion that CSCs are responsible for tumor development including tumor initiation, invasion, angiogenesis, therapy resistance, and recurrence [33][35]. GSCs have been demonstrated to be highly invasive [36], [37]. In fact, invasive glioma cells show tumor stem cell characteristics with neurosphere formation ability and tumorigenicity [34], [38].…”
Section: Discussionmentioning
confidence: 99%
“…This includes the MAGE family of proteins that bind to specific E3 RING ubiquitin ligases and form stable complexes referred to as MAGE-RING ligases (MRLs). A number of proteomic studies have identified many MRLs, including those involving both type I and II MAGEs (including MAGE-A1, -A2, -A3, -A6, -B2, -B18, -C2, -D1, -E1, -F1, -G1, -L2 and NECDIN) that bind to specific E3 RING ligases (including, LNX1, NSE1, PRAJA1, RBX1, TRIM27, TRIM28, and TRIM31) (18, 26, 30-32). MAGEs bind E3 ligases through their MHD that is both necessary and sufficient for binding (18).…”
Section: Mage-ring Ligases (Mrls)mentioning
confidence: 99%
“…During the past decade, emerging evidence supports the notion that cancer stem cells (CSCs) or cancer-initiating cells are responsible for tumor development including invasion and angiogenesis, therapy resistance, and recurrence (3)(4)(5)(6). Glioma stem-like cells (GSLCs) have been demonstrated to possess highly invasive activity (7,8). Besides, the invasive glioma cells present stem cell characteristics with increasing neurosphere formation ability and tumorigenicity (4,9).…”
mentioning
confidence: 99%